2022
DOI: 10.1097/cce.0000000000000616
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics and Outcomes of Patients With Frailty Admitted to ICU With Coronavirus Disease 2019: An Individual Patient Data Meta-Analysis

Abstract: Supplemental Digital Content is available in the text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
31
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 26 publications
(34 citation statements)
references
References 78 publications
2
31
1
Order By: Relevance
“…Furthermore, end-of-life practices during critical illness vary worldwide, and in Latin America, such care restrictions often take longer to implement and occur when the patient is near death ( 25 ). This practice might differ from what is commonly reported in Europe and North America in the pre-COVID-19 period ( 25 ) and might explain our distinct findings from previous reports ( 2 , 3 ).…”
Section: Discussioncontrasting
confidence: 96%
See 4 more Smart Citations
“…Furthermore, end-of-life practices during critical illness vary worldwide, and in Latin America, such care restrictions often take longer to implement and occur when the patient is near death ( 25 ). This practice might differ from what is commonly reported in Europe and North America in the pre-COVID-19 period ( 25 ) and might explain our distinct findings from previous reports ( 2 , 3 ).…”
Section: Discussioncontrasting
confidence: 96%
“…Since the CFS is a feasible and well-known frailty tool in critical care ( 2 , 22 , 23 ), our results encourage its incorporation into the ICU practice. It is also worth mentioning that differently from previous studies ( 3 , 23 ), we determined the prognostic effect of frailty on 6-month mortality, incorporating aspects related to long-COVID complications. Exploring long-term survival is relevant as recent work has indicated that frailty increases the risk of patient-centered adverse outcomes (e.g., functional disability) in COVID-19 ICU survivors after hospital discharge ( 11 ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations